ANALISIS PENGENDALIAN PEMANFAATAN AIR TANAH DI KOTA SORONG - Gedy, Peter Richardo; Mujiati, Mujiati; Safanpo, Apolo (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2023)
In the 2015-2019 National Medium-Term Development Plan (RPJMN), one of the priority locations for the development of an independent and integrated new public city in the Papua Island region is Kota Baru Sorong. In supporting the infrastructure facilities of the new city of Sorong for clean water, in an effort to find clean water, groundwater emerges as a prima donna, becomes our main choice in meeting water needs, of all the advantages possessed by groundwater there are things that we must pay attention to, one of them is only groundwater should be the last option in meeting our water needs after surface water and rainwater. By formulating the groundwater problem, two essential problems arise, namely the existing condition of groundwater use and the role of the government in controlling its use, with the method of collecting observational data and interviews combined with existing secondary data. the role of the government through concepts, actors and mechanisms for controlling groundwater use in the city of Sorong